Comparative Analysis of Accounting Principles in Trading Carbon Emissions for Alternative Mechanism Design - Zhang, Caiping; Randhir, Timothy O. (Journal of Environmental Accounting and Management, 2026)
Carbon emission rights scheme as a market-oriented mechanism is regarded as an effective way to cut down the volumes of greenhouse gases. However, Although International Accounting Standard Board (IASB) and Financial Accounting Standard Board (FASB) have done much work in this field, it appears to have little progress. Therefore, accounting for carbon emission rights has become a dilemma in global accounting area. In this paper, we use a comparative analysis of process features and accounting recognition problems in two allocation schemes: “Cap and Trading Scheme” (CTS) and “Baseline and Credit Scheme” (BCS). We analyze similarities and differences of two schemes that lead to different accounting principles. The research indicate that carbon emission rights, either allowance or credit, have similarity in currency property, although it has different kinds of features. The systematical differences between CTS and BCS lead to basic differences in accounting principles. Under CTS, the different purposes like holding allowance for trading or holding allowance for commitment lead to different ways of accounting recognition. Under BCS, it only needs to recognize credit as a carbon currency. The paper provides a unique perspective to handle accounting principle dilemma of carbon emission rights. The accounting principles are helpful for the enterprises to well manage carbon losses or gains by completely reflecting the whole process of emission rights distribution, trading and delivery. The research results will provide directions for accounting standard setting boards to formulate the accounting standard for carbon emission rights.